European inventory on validation of non-formal and informal learning 2014 : country report Liechtenstein - Annen, Silvia [Verfasser]; Bretschneider, Markus [Verfasser] (My University, 2014)
"Since 2010, the approaches towards validation of non-formal and informal learning in Liechtenstein have mostly stayed the same - regarding the process as well as regarding the use. The most significant innovation was implemented within the higher education system. In 2010, the Law on Higher Education changed admission procedures to a bachelor programme or to further training master programme‚ so that sur dossier became an option (on the basis of a written application), which means on the basis of the validation of prior non-formal or informal learning. This was already informal practice before 2010 (by a flexible interpretation of the phrase in the law that admission could be granted because of the Matura and other qualifications). Through the change of the law, this informal practice of admission to higher or further educational programmes was formalised. Within vocational education and training, the legal regulation regarding validation is still the same as 2010. " (authors' abstract; BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2.1 Westeuropa; Non-formales Lernen; Informelles Lernen; Anerkennung; Liechtenstein